Agroindústria canavieira e unidade de conservação: Impactos Sociais na comunidade de pescadores de Baía Formosa (RN) - Govindin, Julienne Louise dos Santos (2014)
The conservation unities emerged in response to the environmental damages. In the Atlantic Forest of the Brazilian Northeast, the most of the damages come from the sugar-cane agro-industry, especially by the deforestation for the introduction of sugar-cane fields and installation of the industry structure. Besides the damages over the biodiversity, there are critical social problems that affect the communities which survive using directly or indirectly the biome from the Atlantic Forest. The objective of this research is to analyze the social impacts on the fishermen of Baía Formosa/RN generated by the changes and socio-environmental transformations occurred starting the installation of a sugar-cane factory and the creation of a conservation area in the municipality of Baía Formosa/RN community. The research is based on a qualitative and diachronic perspective, for both approach, it was used the method of oral history in conjunction with the literature search and some technical and research tools such as direct observation, interview, records images and recordings . The results show that social and symbolic practices of the community in the conservation unit Mata Estrela last more strongly presented. Today fewer natural resources are used, due to factors such as limit access to forest and disappearance of some natural resources by deforestation. It is believed that the loss of free access to space for the community is the most significant negative impact, as promoted changes in the relationship of the community with the Star Forest that contributed to the fading of their social and symbolic practices. The loss of free access caused the decline in the practice of agriculture, which resulted in the loss of one of the means of social reproduction of the community